Impact of a randomized controlled trial in arsenic risk communication on household water-source choices in Bangladesh - Bennear, L.; Tarozzi, A.; Pfaff, A.; Balasubramanya, Soumya; Ahmed, K.M.; Geen, A. van (Elsevier, 2013)
We conducted a randomized controlled trial in rural Bangladesh to examine how household drinking-water choices were affected by two different messages about risk from naturally occurring groundwater arsenic. Households in both randomized treatment arms were informed about the arsenic level in their well and whether that level was above or below the Bangladesh standard for arsenic. Households in one group of villages were encouraged to seek water from wells below the national standard. Households in the second group of villages received additional information explaining that lower-arsenic well water is always safer and these households were encouraged to seek water from wells with lower levels of arsenic, irrespective of the national standard. A simple model of household drinking-water choice indicates that the effect of the emphasis message is theoretically ambiguous. Empirically, we find that the richer message had a negative, but insignificant, effect on well-switching rates, but the estimates are sufficiently precise that we can rule out large positive effects. The main policy implication of this finding is that a one-time oral message conveying richer information on arsenic risks, while inexpensive and easily scalable, is unlikely to be successful in reducing exposure relative to the status-quo policy.